Die Anwendbarkeit der Behavioral Finance im Devisenmarkt - Thomas Heidorn; Tindaro Siragusano (Hochschule für Bankwirtschaft (HfB), 2004)
Behavioral finance theory is used for the foreign exchange market to show, that the profit of a typical trader is mainly due to the higher number of correct positions. Using behavioral finance the amount of loss trades is larger than 60%, however the individual gains are larger than the losses leading to an overall profit. Using this approach we show, that behavioral finance rules can be quantified and a trading outperformance is possible just using 24h spot rates and 3 day volatilities.
urn:nbn:de:101:1-20080724105
Keywords: G12; G14; 330; behavioral finance; technical trading; foreign exchange market; FX; anchoring; regret avoidance